Review process for IVIg treatment: Lessons learned from INSIGHTS neuropathy study. Issue 5 (October 2018) - Levine, Todd D.; Katz, Jonathan S.; Barohn, Richard; Vaughan, Leslie J.; Dimachkie, Mazen M.; Saperstein, David S.; Mozaffar, Tahseen; Wolfe, Gil I.; Mayo, Matthew S.; Badger, Gary J.; Katzin, Lara; Ritt, Elissa; et al.
Abstract : Background: This project is an effort to understand how orders for IV immunoglobulin (IVIg) are documented and prescribed by physicians, and subsequently, how they are reviewed by insurance companies for the treatment of immune neuropathies. Methods: A panel of neuromuscular specialists reviewed case records from 248 IVIg-naive patients whose in-home IVIg infusion treatment was submitted to insurance for authorization. After reviewing a case record, 1 panelist was asked to make a diagnosis and to answer several questions about the treatment. A second panelist reviewed the original record and follow-up records that were obtained for reauthorization of additional treatments and was asked to determine whether the patient had responded to the treatment. Results: Our specialists believed that only 32.2% of 248 patients had an immune neuropathy and were appropriate candidates for IVIg therapy, whereas 46.4% had neuropathies that were not immune mediated. Only 15.3% of cases met electrodiagnostic criteria for a demyelinating neuropathy. Our specialists believed that 36.7% of 128 cases with follow-up records had responded to therapy. In cases in which the initial reviewer had predicted that there would be a response to IVIg, the second reviewer found that 54% had responded. This is compared with a 27% response rate when the first reviewer predicted that there would be no response ( p = 0.019). Conclusions: Our expert review finds that the diagnosis of immune neuropathies made by providers, and subsequently approved for IVIg therapy by payers, is incorrect in a large percentage of cases. If payers include an expert in their review process, it would improve patient selection, appropriate use, and continuation of treatment with this expensive therapeutic agent.